Addition of immunotherapy to perioperative chemotherapy for resectable gastric and gastroesophageal junction cancer: a meta-analysis of phase 2/3 trials - Lin, Yuxuan; Liao, Yonghe; Shen, Jinhai (Frontiers in Immunology, 2025)
BackgroundThe integration of immune checkpoint inhibitors (ICIs) with perioperative chemotherapy (CT) has become a major focus of clinical research in resectable gastric or gastroesophageal junction (G/GEJ) cancer. Recent phase 2 and 3 trials have reported disparate outcomes, generating considerable debate. To synthesize this evidence, we conducted a meta-analysis to evaluate the efficacy and safety of adding ICIs to CT in this setting.MethodsA systematic literature search of PubMed and major conference proceedings was conducted up to August 15, 2025. Efficacy outcomes included summary relative risks (RRs) for pathological complete response (pCR) and R0 resection rate, and hazard ratios (HRs) for event-free survival (EFS) and overall survival (OS). Safety was assessed using RRs for treatment-related adverse events (AEs).ResultsFour trials (one phase 2 [NEOSUMMIT-01], one phase 2/3 [DANTE], and two phase 3 [KEYNOTE-585, MATTERHORN]), encompassing 2,358 patients, were included. The addition of ICIs to CT significantly improved pCR (RR: 2.80; 95% CI: 1.68–4.67), EFS (HR: 0.76; 95% CI: 0.67–0.87), and OS (HR: 0.78; 95% CI: 0.61–0.99), although it did not increase the R0 resection rate. Regarding safety, the combination did not increase the risk of overall grade 3–5 treatment-related AEs. However, it was associated with a significantly higher risk of grade 3–5 immune-related AEs (RR: 2.88; 95% CI: 1.95–4.24) and treatment-related serious AEs (RR: 1.14; 95% CI: 1.01–1.28).ConclusionThe addition of ICIs to perioperative CT confers significant improvements in pCR, EFS, and OS in resectable G/GEJ cancer, with a generally manageable safety profile. However, longer follow-up is required to validate survival benefits, and the increased risk of immune-related toxicity underscores the need for administration in specialized centers. These findings suggest that perioperative chemo-immunotherapy is a promising treatment strategy, though its definitive role awaits confirmation from ongoing phase 3 trials.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251131385.